Perubahan sosioekonomi terhadap pemilihan pasangan dan pengendalian majlis perkahwinan Melayu di Kuala Lumpur / Hanxiao @ Indah - Hanxiao , Indah (2018)
This research is aimed at analyzing the changes of urban Malays’ spouse selection and wedding organization in Kuala Lumpur, and meanwhile inspecting the impact of socioeconomic factors on the changes which have already happened. The five socioeconomic factors, as the consequences of the urbanization process, refer to education, salary, occupation, residence and family socioeconomic status concretely. This research has been conducted based on the Modernization Theory and models modified from Edwards’s and Yaacob Harun’s models in analyzing the changes of urban Malays’ marriage and family. Two important research methods have been utilized in this research, which are quantitative and qualitative research techniques. Quantitative method has been applied by sending questionnaires to 214 respondents in Kuala Lumpur, referring to 107 Malay couples who just got married in the last two or three years. Qualitative method consists of library research and interviews on 14 Malay couples. Inasmuch as the highest level of urbanization, Kuala Lumpur was chosen to be the study site. This research suggests that significant changes have taken place in urban Malays’ spouse selection. Such changes range from the age at first marriage, the rights of selecting a spouse, ways to find a spouse and spouse selection criteria. In terms of this point, socioeconomic factors have become influential, including education, occupation, salary and family socioeconomic status. Additionally, wedding organization have undergone great changes as well, including the marriage payment, the selection of wedding date and wedding venue, human support system and financial support system vi in organizing wedding. It argues that socioeconomic factors, such as education, occupation, salary, residence and family socioeconomic status are virtually related to aforementioned changes. When this research was carried out, not only the socioeconomic factors have been studied, the social culture factors have also been analyzed. This research reveals that although big changes have already taken place in urban Malay society in Kuala Lumpur, especially in spouse selection and wedding organization, the impact of traditional Malay values, customs and Islam rules still have profound influences on urban Malays. This finding rebuts the Modernization Theory which argues “modern” and “traditional” cannot exist at the same time because these two values are mutually exclusive. But, what is happening in urban Malay society in Kuala Lumpur has proven that “modern” and “traditional” can co-exist harmoniously. Given that in Islamic Malay society, marriage is still the only premise of family formation. Thus, all the procedures relating to marriage and wedding should practice the elements of social-culture which have been accepted by the society from generation to generation.